1994
DOI: 10.1021/ed071p9
|View full text |Cite
|
Sign up to set email alerts
|

Concept Maps as a Tool To Assess Learning in Chemistry

Abstract: Study of the use of concept maps drawn from clinical interviews as tools to assess learning in two groups of chemistry students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 24 publications
0
43
0
8
Order By: Relevance
“…This finding is consistent with David Ausubel's theory of meaningful learning. In terms of Ausubel's theory, if students manage to meaningfully incorporate new knowledge into existing knowledge structure (background knowledge), and then we would expect to see relationships between conceptual knowledge after instruction and achievement [1,43]. Indeed, the present study found that background knowledge is a significant predictor of genetics problem solving ability.…”
Section: Discussionmentioning
confidence: 61%
“…This finding is consistent with David Ausubel's theory of meaningful learning. In terms of Ausubel's theory, if students manage to meaningfully incorporate new knowledge into existing knowledge structure (background knowledge), and then we would expect to see relationships between conceptual knowledge after instruction and achievement [1,43]. Indeed, the present study found that background knowledge is a significant predictor of genetics problem solving ability.…”
Section: Discussionmentioning
confidence: 61%
“…Our research and the research of others indicate that while the latter factors are in many cases significant factors influencing achievement, they are probably not the most important factors (Carey, 1985;Donaldson, 1978;Metz, 1997). For example, in a study with Ph.D. students in chemistry at Cornell University, the number and variety of misconceptions after carefully designed lectures on gas chromatography was similar to that evidenced before the lectures (Pendley, Bretz, & Novak, 1994). After carefully designed and executed eighth grade science lessons on the particulate nature of matter, students evidenced a greater number and variety of misconceptions than scientifically accepted conceptions (Bartow, 1981).…”
Section: The Problem Of Faulty Conceptual Frameworkmentioning
confidence: 81%
“…Superordinate concepts are relatively few in number in any knowledge domain, so most learning in usually subsumptive learning. Superordinate learning normally contributes significantly to development of cognitive structure, and this characterizes the knowledge of experts (Chi, Feltovich, & Glaser, 1981;Novak & Iuli, 1995;Pendley, Bretz, & Novak, 1994). Finally, (4) integrative reconciliation may be required, or the form of meaningful learning where concepts or propositions in two somewhat different knowledge domains are seen as clearly similar and related, or clearly different and unrelated.…”
Section: Why Meaningful Learning Is Essential To Remediate Liph's Andmentioning
confidence: 99%
“…Hasil penelitian tentang kesulitan belajar ilmu kimia menunjukkan banyak siswa yang dapat dengan mudah mempelajari matapelajaran lain, tetapi mengalami kesulitan dalam memahami konsep-konsep dan prinsip-prinsip kimia [2,3]. Hasil penelitian lainnya menunjukkan bahwa pada umumnya siswa cenderung belajar ilmu kimia dengan hafalan daripada secara aktif mencari untuk membangun pemahaman sendiri terhadap konsep kimia tersebut [4].Pemahaman setiap orang mengenai konsep dinamakan konsepsi. Kesalahpahaman konsepsi dinamakan miskonsepsi [5].…”
unclassified